Objetivos de desenvolvimento sustentável e desafios decorrentes das oportunidades escolares no ensino fundamental brasileiro - Milko Matijascic; Carolina Esther Kotovicz Rolon (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper investigates the intersectional inequalities in the Brazilian primary and lower secondary school levels in 2017, comparing them with those observed in 1997. To do so, it analyses the indicators of goal 4.1 of the Sustainable Development Goals (SDGs), namely, the completion rates of primary and lower secondary levels and the percentage of students who reached the level of performance considered satisfactory in the Reading and Mathematics tests of the Basic Education Assessment System (Saeb), from 1997 and 2017. The intersectionality of the categories of sex, race, and family per capita income and sex, Brazilian regions and rurality proved to be signifi cant to explain the inequalities in the completion rates of primary school in 1997 and of the lower secondary level in 1997 and in 2017, demonstrating the importance of ceasing educational inequalities in their dynamics. The imbrications of the categories of sex, race and large Brazilian regions and sex, large Brazilian regions and rurality were signifi cant in understanding the inequalities in student performance at the end of both primary and lower secondary school cycles in 1997 and 2017. By shedding light on intersectional inequalities in primary and lower secondary education, the results of this research contribute to the monitoring of goal 4.5 of the SDG which aims to overcome educational inequalities.
Keywords: I29; 330; Sustainable Development Goals; inequality of educational opportunities; primary and lower secondary schools; Basic Education Assessment System (Saeb)